A 0.6-V high reverse-isolation through feedback self-cancellation for single-stage noncascode CMOS LNA - Tran, T. T. N. (2013)
In many designs, a low supply voltage is selected for efficient use of power. However, this often leads to low reverse-isolation which is critical to the RF front–end circuits and particularly to the low-noise amplifier (LNA). In this letter, a fully integrated differential low-voltage CMOS LNA with high reverse-isolation is presented. This LNA makes use of the single-stage noncascode structure and the capacitive cross-coupling (CCC) technique. The CCC technique has been utilized in many LNA designs. However, in all of the reported works using CCC, the CCC technique was mainly used to improve the noise figure (NF), not the reverse-isolation. The poor reverse-isolation problem in single-stage noncascode structure has never been analyzed in the capacitive cross-coupling cascaded low noise amplifier (CCCLNA). This work shows a novel analysis on the feedback self-cancellation mechanism to improve the reverse-isolation. Other analyses on input matching, gain and NF were also performed to show the feasibility of using CCC technique for the low-voltage LNA as well as the advantages of the CCCLNA over the conventional common-source and common-gate (CG) LNA. The LNA consumes only 0.5 mW from 0.6 V supply voltage. It achieves a gain of 14 dB and a NF of 3.55 dB.